Biohydrogen - Rögner, Matthias (De Gruyter, 2015)
Biohydrogen is considered the most promising energy carrier and its utilization for energy storage is a timely technology. This book presents latest research results and strategies evolving from an international research cooperation, discussing the current status of Biohydrogen research and picturing future trends and applications.
Keywords: Hydrogen -- Biotechnology.; Hydrogen as fuel.; Biomass energy.; elektronické knihy; electronic books